Freedomland [videorecording (DVD)] - Roth, Joe, 1948-; Jackson, Samuel L.; Moore, Julianne; Falco, Edie; Price, Richard, 1949- (Sony Pictures Home Entertainment, 2006)
As a housing project cop who's respected for keeping the peace and being fair with the residents, Lorenzo Council stumbles onto the case of an apparent carjacking and child abduction one night that throws the projects into turmoil. But there's something strange in the details Brenda Martin slowly brings to light regarding her abductor and her missing child. The criminal investigation into the alleged kidnapping ignites long-simmering racial tension between two neighboring New Jersey towns.